Gastric Perforation Associated with Tuberculosis: A Case Report - Richdeep S. Gill; Sumeet S. Gill; Harshdeep Mangat; Sarvesh Logsetty (Case Reports in Medicine)
Gastric tuberculosis is a rare presentation of tuberculosis infection. Gastric perforation associated with tuberculosis is exceedingly rare with five previously published cases. We present a case of a male patient that developed presumed gastric tuberculosis secondary to pulmonary tuberculosis infection. He subsequently developed gastric perforation and sepsis, for which he was treated both surgically and medically. Despite ongoing antituberculosis treatment, the patient's condition worsened and the patient died secondary to multiorgan failure. This case highlights gastric perforation as a rare but devastating complication of pulmonary tuberculosis.